TINDAK TUTUR EKSPRESIF DI AKUN INSTAGRAM @kampuszone - Pangesti, Nurma Indah; Rosita, Farida Yufarlina (Hasta Wiyata, 2019)
This study is aimed to analyze a speech act in @kampuszone instagram account, especially expressive speech act. The method of this study is qualitative-descriptive. The data of this study are utterances that is uploaded in @kampuszone instagram account from January until March, 2019. Data collection technique are carried out with documentation. Outlined into four steps, namely data collection, data reduction, data display, and data verification. The result of this study show that the posts in @kampuszone instagram account have many expressive speech act. There are complaint, spirit, hope, sadness, thank goodness, boredom, admiration, disagreement, and agreement. The majority of posts in @kampuszone instagram account is spirit. There are many spirit is given through @kampuszone instagram posting. Spirit for students to study harder, spirit for having success, spirit to fight the college, etc.